Removal of Disperse Blue 56 from synthetic textile effluent using ionic flocculation - R. P. F. Melo; S. K. S. Carmo; E. L. B. Barros; A. G. Câmara; S. K. S. Nunes; E. L. Barros Neto (Water Science and Technology, 2021)
The textile industry is one of the main generators of industrial effluent due to the large volumes of water containing a wide variety of pollutants, including dyes. Thus, the present study aimed to remove the Disperse Blue 56 dye present in synthetic textile effluent using ionic flocculation through surfactant flocs produced from animal/vegetable fat, assessing the system at different surfactant concentrations and temperatures. The process kinetics, adsorption mechanism and equilibrium were evaluated. The results show that the kinetics was better described by the Elovich model when compared to pseudo-first order and pseudo-second order models, indicating that chemical adsorption occurs during the process. The study of the adsorption mechanism obtained lower outer layer diffusivities than their intra-particle counterparts, demonstrating that the dye transport to the surfactant floc is controlled through the outer layer. The Langmuir isotherm was suitable for equilibrium data and the separation factor calculated showed that the isotherm is classified as favorable. Dye removal efficiency reached 87% after 360 minutes of contact between the effluent and the surfactant flocs, indicating that ionic flocculation is an efficient alternative in the treatment of textile effluent containing disperse dye. HIGHLIGHTS Ionic flocculation was studied for removal of a disperse dye from water.; Surfactants obtained from animal/vegetable fat are used for wastewater treatment.; Kinetic, diffusion mechanism and equilibrium were evaluated.; Temperature does not have considerable influence on the process.; The proposed methodology allows a removal efficiency of 87%.;